Budidaya Ayam Kampung Terintegrasi untuk Mengatasi Stunting di Desa Candisari, Kecamatan Windusari, Kabupaten Magelang - Nur Rasminati; Setyo Utomo; Bambang Nugroho (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
Candisari village is one of the villages in Windusari District, Magelang which has a problem of high stunting children. Stunting is a major threat to the quality of Indonesian society. This activity aims to assist the government in overcoming stunting through integrated native chicken cultivation. The methods used are raising awareness in the community, training and making demonstration plots. The target group is mothers who have children under five years old (toddlers) who are indicated to be stunted. The training carried out was how to raise native chickens integrated with vegetable crops, making supplementary food formulas for toddlers, demonstration plots of raising chickens integrated with vegetable plants. Chicken rearing activities are carried out by providing stimulus to 30 hens and 3 roosters. The results of the assistance reduced the stunting rate from 79 toddlers at the beginning of the activity to 46 toddlers at the end of the activity. Based on observations, all native chickens (100%) have laid eggs, with 100% hatchability and an average number of chicks of 10. In the cultivation of vegetable plants in the yard, it has succeeded 90% and has started to harvest the mustard, tomato and chili plants. The conclusion from this activity is that integrated chicken farming has a positive impact on reducing stunting rates.